2021
DOI: 10.1002/ldr.4119
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐physiological responses of Calamagrostis epigejos L (Roth) and Solidago gigantea Aition to complex environmental stresses in coal‐mine spoil heaps

Abstract: We present a study of short and long‐term responses of photosynthetic apparatus and anti‐oxidant capacity to complex abiotic stresses of Calamagrostis epigejos and Solidago gigantea commonly occurring in seminatural habitats and novel ecosystems of coal‐mine spoil heaps. Drought/salinity and elevated temperature were dominant abiotic stressors triggering both species‐ and habitat‐specific responses, confirmed by ChlF induction curves analysis. Although in both species a decrease in net photosynthetic rate (A) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…The study site was the "So snica" hard coal post-mine spoil heap in Gliwice and Zabrze (50 16 0 22 00 N, 18 44 0 43 00 E), Upper Silesian Coal Basin, Southern Poland. The regional climate is classified as temperate, with an average annual precipitation of 727 mm and an average annual temperature of 8.5 C. Hard coal has been mined for over 250 years and covers approximately 170 hectares with a height of more than 30 m (Kompała-Bąba et al, 2021). The spoil heap is composed of carboniferous rocks, primarily shale, sandstone, and their conglomerate (Prasad et al, 2018).…”
Section: Study Sitementioning
confidence: 99%
“…The study site was the "So snica" hard coal post-mine spoil heap in Gliwice and Zabrze (50 16 0 22 00 N, 18 44 0 43 00 E), Upper Silesian Coal Basin, Southern Poland. The regional climate is classified as temperate, with an average annual precipitation of 727 mm and an average annual temperature of 8.5 C. Hard coal has been mined for over 250 years and covers approximately 170 hectares with a height of more than 30 m (Kompała-Bąba et al, 2021). The spoil heap is composed of carboniferous rocks, primarily shale, sandstone, and their conglomerate (Prasad et al, 2018).…”
Section: Study Sitementioning
confidence: 99%
“…Our obtained results indicate that biodiversity does not depend on the method of reclamation, which translates into key ecosystem functions, such as CO 2 storage and tree productivity [68]. However, this may be due to having access to similar propagules and the extent of the environmental adaptation of the plants to the environmental conditions of spoil heaps [18].…”
Section: Discussionmentioning
confidence: 76%
“…A comprehensive understanding of the technical aspects involved in handling spoil heaps, and a recognition of their ecological significance in urban and industrial settings, is essential. This knowledge empowers individuals and communities to actively engage in supporting and restoring ecological functions, such as plant community succession, dynamic soil processes, soil microbiological activity, afforestation efficiency, biomass production, carbon (C) sequestration [3], the development of biodiversity [17], as well as the response of the plants to environmental stress factors [18]. A large body of research has shown that biodiversity loss can reduce ecosystem functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Calamagrostis epigeios is a perennial herbaceous plant of the Poaceae family with a long creeping rhizome. The plant tolerates salinity, quickly captures substrates, and is resistant to the influence of heavy metals (Beshley et al, 2010;Beshley, 2011;Kompała-Bąba et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%